1997
DOI: 10.1177/1532673x9702500403
|View full text |Cite
|
Sign up to set email alerts
|

Presidential Use of Executive Orders, 1953-1994

Abstract: The frequency with which presidents issue executive orders is an important area of inquiry for students of executive politics, because this instrument can shape policy in a quick, direct manner that is outside the purview of the legislative arena. We construct a probabilistic-based empirical model that is used to explain variation in the number of presidential executive orders issued during the 1953-1994 annual period. Using event count regression techniques, these results indicate that the use of executive or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 26 publications
5
108
0
Order By: Relevance
“…This supports our contention that the state of the economy serves as a constraint factor that encourages presidents to issue a higher volume of executive orders than they would otherwise. Surprisingly, we fail to find empirical evidence that the partisan seat margin in the House and Senate enjoyed by presidents affects their willingness to issue executive orders during the institutional presidency, as noted in prior research on this topic (Krause and Cohen 1997). Furthermore, neither the growth in the executive branch bureaucracy nor the first year of a president's tenure in office result in a statistically meaningful effect on the frequency of executive order issuance.…”
Section: M1 M2mentioning
confidence: 45%
“…This supports our contention that the state of the economy serves as a constraint factor that encourages presidents to issue a higher volume of executive orders than they would otherwise. Surprisingly, we fail to find empirical evidence that the partisan seat margin in the House and Senate enjoyed by presidents affects their willingness to issue executive orders during the institutional presidency, as noted in prior research on this topic (Krause and Cohen 1997). Furthermore, neither the growth in the executive branch bureaucracy nor the first year of a president's tenure in office result in a statistically meaningful effect on the frequency of executive order issuance.…”
Section: M1 M2mentioning
confidence: 45%
“…Senate ideology is also a driving factor in the president's decision to nominate an individual to the Supreme Court: particularly when the president is "constrained," the median senator's ideology influences who a president will nominate to the Supreme Court (Moraski and Shipan 1999). Despite evidence to the contrary (Krause and Cohen 1997), Deering and Maltzman (1999) demonstrate that presidents issue executive orders in the face of a Congress hostile to them, but only if Congress is unlikely to overturn them. 4.…”
Section: Notesmentioning
confidence: 92%
“…The role of divided and unified government is important to consider even in a more descriptive study such as this in providing the basic contours of how presidents are using executive orders. The majority of the research has concluded that presidents issue more executive orders during unified government than divided government, which runs counter to conventional wisdom (Gleiber and Shull 1992;Howell 2003;Krause and Cohen 1997;Mayer 1999Mayer , 2001and Warber 2006). On the contrary, there is evidence indicating that presidents are more likely to issue all types of executive orders to "circumvent a [politically] hostile Congress" (Deering and Maltzman 1999, 767).…”
Section: Targeting the Public With Executive Ordersmentioning
confidence: 82%